Measurement of scattering and absorption properties of dust aerosol in a Gobi farmland region of northwestern China – a potential anthropogenic influence - J. Bi; J. Huang; J. Shi; Z. Hu; T. Zhou; G. Zhang; Z. Huang; X. Wang; H. Jin (Atmospheric Chemistry and Physics, 2017)
We conducted a comprehensive field campaign to explore the optical characteristics of mineral dust in Dunhuang farmland near the Gobi Desert of northwest China during spring of 2012. The day-to-day and diurnal variations of dust aerosol showed prominent features throughout the experiment, primarily attributable to frequent dust events and local anthropogenic emissions. The overall average mass concentrations of the particulate matter with an aerodynamic diameter less than 10 µm (PM10), light scattering coefficient (σsp, 670), absorption coefficient (σap, 670), and single-scattering albedo (SSA670) were 113 ± 169 µg m−3, 53.3 ± 74.8 Mm−1, 3.2 ± 2.4 Mm−1, and 0.913 ± 0.05, respectively, which were comparable to the background levels in the southern United States but smaller than those in the eastern and other northwestern Chinese cities. The anthropogenic dust produced by agricultural cultivations (e.g., land planning, plowing, and disking) exerted a significant superimposed effect on high dust concentrations in Dunhuang farmland prior to the growing season (i.e., from 1 April to 10 May). Strong south valley wind and vertical mixing in daytime scavenged the pollution, and the weak northeast mountain wind and stable inversion layer at night favorably accumulated the air pollutants near the surface. In the afternoon (13:00–18:00 LT, local time), mean SSA670 was 0.945 ± 0.04 predominantly from dust particles, whereas finer particles and lower SSA670 values ( ∼  0.90–0.92) were measured at night, suggesting the potential influence by the mixed dust pollutants. During a typical biomass burning event on 4 April 2012, σap, 670 increased from  ∼  2.0 to 4.75 Mm−1 and SSA670 changed from  ∼  0.90 to ∼  0.83, implying remarkable modification of aerosol absorptive properties induced by human activities. The findings of this study would help to advance an in-depth understanding of the interaction among dust aerosol, atmospheric chemistry, and climate change in a desert source region.